(untitled) (Research, Society and Development, 2019)
In this article, we analyze the dissertations of the Postgraduate Program in Professional Education - PPGEP / IFRN, belonging to Research Line 2: “Teacher Training and Pedagogical Practices”, defended in 2018. With the objective of analyze and discuss the perspective of the interdisciplinary theme. The research took place through a survey in the Catalog of Theses and Dissertations of the Portal of the Coordination of Improvement of Higher Education - CAPES. As for the results, we found 7 dissertations, of which two did not mention our object of analysis, while the others dialogued with several areas of knowledge, which approach the construction of a more globalized knowledge.